Stress Fracture Tibia among Military Recruits Management by Patellar Tendon Bearing Cast - Khan, Mohammad Shahnewaz Hossain; Karim, Rezaul; Eqbal, SM; Masum, Abdullah; Kowser, ASM (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Lower limb overuse injuries are common features of military training. Female recruits have significantly higher incidence of fracture than male recruits. In addition to the cost and time of rehabilitation, injury leads to disillusionment among recruits. Conventionally stress fracture tibia is treated with long leg posterior cast for 6-8 weeks but little is known about the length of time required for rehabilitation and to return to pre-injury level. Objectives: To see the outcome of management of stress fracture tibia among military recruits treated with Patellar Tendon Bearing (PTB) cast for 8 weeks and to find out the rehabilitation time to return to pre-injury level. Materials and Methods: This prospective study was conducted in Combined Military Hospital, Bogura, Bangladesh, from January 2015 to December 2016. Out of 2600 recruits 74 (male 60 females 14) were diagnosed as case of stress fracture tibia during the period. They were treated by PTB cast for 08 weeks and their treatment and rehabilitation to pre-injury level (follow-up) were recorded prospectively. Results: Total 85 patients were clinically suspected to have stress fracture tibia, out of them 74(87.06%) patients were finally diagnosed as case of stress fracture. Of these 74 patients 44(59.46%) were diagnosed by initial x-ray and 30(40.54%) were diagnosed by MRI scan. Prevalence of stress fracture in male was 2.45% and in female recruits 9.33%, overall prevalence was 2.85%.About 56(75.67%) patients developed stress fracture in 0-8 weeks of training, mean rehabilitation time to return to pre-injury level was 15.51 weeks, there was no recurrence of stress fracture and all the patients completed 12 months training, none of them was relegated or withdrawn from training on medical ground. Conclusion:Patellar tendon bearing cast is an effective, technically simple method for treating stress fracture of tibia in military recruits with excellent outcome. This method not only treats the fracture but also prevents depressive disorders. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 196-199